Den arabiske telefon - Krimiparodier og litterær åndsnærværelse hos marokkaneren Driss Chraïbi - Jørgensen, Steen Bille (Passage - Tidsskrift for litteratur og kritik, 2014)
Steen Bille Jørgensen: “The Arab Telephone: Crime Parodies and Literary Presence of Mind in the Work of Moroccan Novelist Driss Craïbi” Telephones play a central role in the work of the Moroccan novelist Driss Chraïbi. As a francophone writer spending most of his life in France, the writer’s meta-literary crime parodies about Inspecteur Ali integrate telephones at a structural and thematic level to invite the reader to reflect on the relation between the oral Arabic culture and the western crime novel. With a point of departure in the French notion of “téléphone arabe” (Chinese whispers) the poetics of the novel is focusing on its capacity to deal indirectly with the experience of proximity and distance. This problem appears already in the partly autobiographical La Civilisation ma mère and is developed throughout the work. Though Chraïbi critically points to ideological aspects of a paternalistic culture, his development of the Inspecteur Ali figure mainly leads the occidental reader to consider the importance of bodily experience and the spoken word (a fortiori oral literature) with its imaginary-fantasmagorical and fictional implications. Thus the telephone appears to be an ambiguous device that on the one hand provokes fragmentation – mainly related to the western civilisation – but on the other hand points to the foundation of an ethos related to listening and more generally an individual presence of mind.